Pengaruh Literasi Digital Terhadap Keterampilan Penulisan Surat dalam Pembelajaran Bahasa Indonesia Mahasiswa STIE SAK Tahun 2022 - Al Fadli Al Fadli (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2023)
This study aims to determine: 1) STIE-SAK students' digital literacy skills, 2) STIE-SAK students' letter writing skills, 3) The effect of digital literacy skills on STIE-SAK students' letter writing skills. This type of research is ex-post facto. The population in this study were all STIE-SAK students. The total population in this study were 350 students. While the sample in this study were 75 students. The sampling technique used in this study was purposive sampling, namely random sampling without regard to strata in the population. This research instrument uses a questionnaire, tests and documentation. The collected data was processed using descriptive statistical analysis and inferential statistical analysis. Based on the results of the descriptive analysis, students' digital literacy skills are included in the medium category with a percentage of 70% and narrative writing skills are included in the medium category with a percentage of 72.6. Based on the results of inferential statistics by testing the hypothesis, the calculation results are obtained, namely tcount = 0.176 while ttable = 1.995 for a significance level of 5%. Because tcount is smaller than ttable, it can be concluded that H0 is accepted and HI is rejected. This means that there is no positive and significant effect of digital literacy skills on STIE-SAK students' letter writing skills.